2018
DOI: 10.1016/j.idairyj.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sonication on the viscosity of reconstituted skim milk powder and milk protein concentrate as influenced by solids concentration, temperature and sonication

Abstract: 14Skim milk powder (SMP) and milk protein concentrates (MPCs) are manufactured by 15 evaporation followed by spray drying and are widely used as functional and nutritional 16 ingredients. This study investigated the effects of temperature (40 to 60 °C) and total solids 17 content (TS) on the viscosity of reconstituted MPC (rMPC) (≥30 % TS) and SMP (rSMP) (≥46 18 % TS) in laboratory conditions. Additionally, the influence of sonication in batch (70 % 19 amplitude) and flow through systems (90% amplitude) was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
4
7
0
1
Order By: Relevance
“…Falcone et al suggested that the change in apparent viscosity and shear stress is closely related to the shear rate, and the change in apparent viscosity and shear stress might be caused by changes in the shape of CN and other dispersion system particles during enzymatic hydrolysis 53 . Deshpande et al also reported that the viscosity of dairy products changed because the shear stress destroyed the non-covalent interaction that formed the aggregates 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Falcone et al suggested that the change in apparent viscosity and shear stress is closely related to the shear rate, and the change in apparent viscosity and shear stress might be caused by changes in the shape of CN and other dispersion system particles during enzymatic hydrolysis 53 . Deshpande et al also reported that the viscosity of dairy products changed because the shear stress destroyed the non-covalent interaction that formed the aggregates 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Ultrason uygulamasının süt ürünlerinde viskoziteyi azaltmasına ilişkin başka çalışmalar da mevcuttur. Deshpande ve Walsh [45] ultrason uygulamasının gerek kesikli gerekse sürekli sistemde rekonstitüye süt proteini konsantratı ve rekonstitüye yağsız sütün viskozitesini önemli düzeyde düşürdüğünü ortaya koymuşlardır. Araştırmacılar viskozitedeki azalmanın ultrason uygulaması nedeniyle protein agregatlarının parçalanmasıyla birlikte artan çözünürlüğün bir sonucu olabileceğini belirtmişlerdir.…”
Section: Fonksiyonel öZelliklerin Değiştirilmesiunclassified
“…Regardless of the mode of concentration, the viscosity of casein micelle suspensions increases with concentration, with a dramatic change from a Newtonian to a non-Newtonian behavior (Karlsson et al, 2007;Dahbi et al, 2010;Krishnakutti Nair et al, 2014). Similarly, the viscosity of reconstituted MPC also increases with protein concentration, and it can be altered by modifications to the serum (Deshpande and Walsh, 2018;Lin et al, 2018). The semi-empirical equation has been used to describe the dependence of viscosity as a function of concentration, with a maximum packing volume fraction for casein micelles of about 0.79 (Snoeren et al, 1982).…”
Section: Colloidal Properties Of Casein Micelles In Concentrated Milkmentioning
confidence: 99%